2016
DOI: 10.1016/j.jamcollsurg.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Perihilar Cholangiocarcinoma: Number of Nodes Examined and Optimal Lymph Node Prognostic Scheme

Abstract: BACKGROUND The role of routine lymphadenectomy for perihilar cholangiocarcinoma is still controversial and no study has defined the minimum number of lymph nodes examined (TNLE). We sought to assess the prognostic performance of American Joint Committee on Cancer/Union Internationale Contre le Cancer (7th edition) N stage, lymph node ratio, and log odds (LODDS; logarithm of the ratio between metastatic and nonmetastatic nodes) in patients with perihilar cholangiocarcinoma and identify the optimal TNLE to accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 47 publications
5
45
0
1
Order By: Relevance
“…The pooled weighted rate of involvement of each LNS was calculated separately for pEHC (four studies, 519 patients), mEHC (five studies, 132 patients) and dEHC (10 studies, 642 patients). Data on the rate of involvement of each LNS according to the pT stage were available only for dEHC (pT1‐2: three studies, 30 patients; pT3‐4: three studies, 61 patients) (Table , Figs –S8).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled weighted rate of involvement of each LNS was calculated separately for pEHC (four studies, 519 patients), mEHC (five studies, 132 patients) and dEHC (10 studies, 642 patients). Data on the rate of involvement of each LNS according to the pT stage were available only for dEHC (pT1‐2: three studies, 30 patients; pT3‐4: three studies, 61 patients) (Table , Figs –S8).…”
Section: Resultsmentioning
confidence: 99%
“…Bagante et al . revealed that the overall survival of N0 patients improved as the number of retrieved LNs increased, whereas the influence of retrieved LNs on survival of N+ patients was slight . Therefore, the impact of retrieved LNs counts on survival was better embodied in N0 patients.…”
Section: Discussionmentioning
confidence: 95%
“…There have been plenty of studies to reveal the pivotal prognostic factors of perihilar cholangiocarcinoma patients with LN metastasis. The prognostic value of LN ratio, number of retrieved LNs and number of positive LNs were validated and compared several times in recent studies . No matter the studies on LN ratio, the number of retrieved LNs or the number of positive LNs, the focus of attention was always on patients with LN metastasis, and studies on patients without LN metastasis are still rare.…”
Section: Introductionmentioning
confidence: 99%
“…16) metastases . Bagante et al reported that tumor metastases in lymph node Nos. 9, 14, and 16 are found in 21.7% (5 of 23) of patients with HCCA and indicated that extended lymphadenectomy including para‐aortic and superior mesenteric nodes may yield an accurate tumor stage and improve the HCCA patient's survival with acceptable postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: AJCC, American Joint Committee on Cancer; MA, mucinous adenocarcinoma the tumor-infiltrated lymph nodes, and consequently, extended lymphadenectomy should be implemented to remove all potentially involved lymph nodes (including No. 8,9,12,13,14, and 16 nodes) and thereby attempt to prolong these patients' survival. Through these techniques, the radicality of laparoscopic resection for Bismuth type III and IV HCCA can be greatly improved, realizing the desire of minimal invasive surgery in patients with HCCA.…”
Section: Discussionmentioning
confidence: 99%